The Efficacy of Psychological Capital Intervention (PCI) for Depression From the Perspective of Positive Psychology: A Pilot Study - Song, Ruijun; Sun, Nana; Song, Xuhong (Frontiers in Psychology, 2019)
Extensive psychological interventions primarily target the negative symptoms of depression and the deficits in positive resources have been systematically neglected. So far, little attention has been devoted to psychological capital (PsyCap) intervention from the perspective of developing positive resources. The aim of the present pilot study was to evaluate the efficacy of psychological capital intervention (PCI) for depression in a randomized controlled trial. A total of 56 patients were randomized to either care as usual (CAU) for normal medication or psychological capital intervention (PCI) group, where the normal medication was supplemented with the PCI. Participants were assessed at pre- and post-treatment, as well as 6-month follow-up, on measures of depressive symptoms and PsyCap. The PCI group displayed significantly larger improvements in PsyCap and larger reductions in depression symptoms from pre- to post treatment compared to control group. Improvements were sustained over the 6-month follow-up period. Targeting the positive resources intervention in the PCI may be effective against the treatment of depression.